Subsurface deposition of Cu-rich massive sulphide underneath a Palaeoproterozoic seafloor hydrothermal system—the Red Bore prospect, Western Australia - Agangi, Andrea; Reddy, Steven; Plavsa, D.; Vieru, C.; Selvaraja, V.; LaFlamme, C.; Jeon, H.; Martin, L.; Nozaki, T.; Takaya, Y.; Suzuki, K. (Springer, 2018)
The Proterozoic Bryah and Yerrida basins of Western Australia contain important base and precious metal deposits. Here we present microtextural data, trace element and S isotope analyses of massive sulphide mineralisation hosted in Palaeoproterozoic subvolcanic rocks (dolerite) recently discovered at Red Bore. The small-scale high-grade mineralisation, which extends from the sub-surface to at least 95 m down-hole, is dominated by massive chalcopyrite and contains minor pyrite and Bi-Te-(Se) phases. Massive sulphide mineralisation is surrounded by discontinuous brecciated massive magnetite, and a narrow (< 2 m) alteration halo, which suggests very focussed fluid flow. Laser ablation ICP-MS analyses indicate that chalcopyrite contains up to 10 ppm Au and in excess of 100 ppm Ag. Sulphur isotope analyses of pyrite and chalcopyrite indicate a narrow range of δ34SVCD (− 0.2 to + 4.6 ‰), and no significant mass-independent fractionation (− 0.1 < Δ33S < + 0.05 ‰). Re-Os isotope analyses yield scattered values, which suggests secondary remobilisation. Despite the geographical proximity and the common Cu-Au-Ag association, the mineralisation at Red Bore has significant differences with massive sulphide mineralisation at neighbouring DeGrussa, as well as other massive sulphide deposits around the world. These differences include the geometry, sub-volcanic host rocks, extreme Cu enrichment and narrow δ34S ranges. Although a possible explanation for some of these characteristics is leaching of S and metals from the surrounding volcanic rocks, we favour formation as a result of the release of a magmatic fluid phase along very focussed pathways, and we propose that mixing of this fluid with circulating sea water contributed to sea floor mineralisation similar to neighbouring VHMS deposits. Our data are permissive of a genetic association of Red Bore mineralisation with VHMS deposits nearby, thus suggesting a direct connection between magmatism and mineralising fluids responsible for VHMS deposition at surface. Therefore, the Red Bore mineralisation may represent the magmatic roots of a VHMS system.